The Digital Transformation of Land and Building Tax Payments with Predictive Systems - Wibisono, Bagas; Rohman, Abdul (Jurnal Sistem Cerdas, 2024)
Digital transformation in the tax payment sector is an essential step to enhance transparency and accountability. This research aims to develop and implement a predictive information system that can predict the payment behavior of Land and Building Tax in Village. The main problem faced is the often slow and non-transparent payment process, as well as the risk of errors or payment defaults. The developed information system uses historical data analysis methods with predictive algorithms to project the future behavior of taxpayers. This system is also equipped with a real-time validation feature to improve accuracy and efficiency in managing payment data. The results show that the predictive information system can provide early warnings related to payment delays and reduce potential errors in recording Land and Building Tax payments. In conclusion, the application of predictive technology in the Land and Building Tax payment system in Village successfully improves transparency, accountability, and efficiency, providing an innovative solution for village tax administration issues.